An Investigation into Helicobacter pylori Treatment Outcomes and Host Responses - FitzGerald, Rebecca (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Helicobacter pylori (H. pylori) is a helical, gram-negative, micro-aerophilic bacterium that infects approximately 50% of the world?s population. Although many of those infected will be asymptomatic, H. pylori increases the risk of developing peptic ulcers, gastric cancer, and mucosa-associated lymphoid tissue (MALT) lymphoma. H. pylori is heavily adapted to colonise the stomach and will persist continuously unless treated. The emergence of antibiotic resistant strains has made treating H. pylori more complicated. The European registry on H. pylori management (Hp-EuReg) was founded in 2013 to collect real-world clinical treatment and eradication data from 30 different countries across Europe. In Chapter 3, an audit of Irish data in the Hp-EuReg was performed to evaluate H. pylori treatment regimens and eradication rates from 2013-2022. Using the modified intention-to-treat (mITT) protocol, 1,000 first line treatments were analysed, with an overall eradication rate of 80.1%. The most prescribed first line treatment was clarithromycin and amoxicillin triple therapy with an eradication rate of 81.4%. Increased treatment duration and high dose PPI were associated with better first line eradication rates. Furthermore, first-line eradication rates significantly increased from 74.5% to 81.6% following publication of the Irish guidelines on the management of H. pylori in 2017. The overall eradication rates for second line and rescue therapies were 64.4% (N=90) and 61.9% (N=21), respectively. Host-directed therapies are treatments that alter the host?s biological pathways. To identify potential targets for host-directed therapies, host-pathogen interactions need to be better understood. The aim of Chapter 4 was to investigate the role of the Notch signalling pathway during H. pylori infection. The Notch pathway is a highly conserved signalling pathway that participates in cell proliferation, maintenance, and differentiation. It was found that H. pylori infection led to downregulated mRNA expression of the Notch associated transcription factor HES1 in gastric epithelial cells and gastric biopsy tissue. HES1 protein was also downregulated in gastric epithelial cells infected with H. pylori. HES1 was over-expressed in gastric epithelial cells and RNAseq was performed. This identified further genes that are impacted by H. pylori mediated HES1 downregulation, such as FOS, IL-8, and CCL20. In macrophages, H. pylori infection was associated with an increase in the expression for the Notch ligands JAG1 and DLL4 and the associated transcription factor HEY1. These results indicate a cell specific role for Notch signalling factors during H. pylori infection. The aim of Chapter 5 was to investigate the role of histone modifying components and inflammatory caspases in H. pylori infection. H. pylori down-regulated expression of the polycomb repressive complex 2 component EED and upregulated expression of the histone demethylase KDM6B in gastric epithelial cells, gastric biopsy tissue and in macrophages. Caspase 4 is an inflammatory caspase that is associated with production of the non-canonical inflammasome. Infection with H. pylori led to an increase in Caspase4 expression in human macrophages. Caspase-11 is the murine homolog of human Caspase 4. Bone marrow derived macrophages from wild-type and caspase 11-deficient (Casp11-/-) mice were infected with H. pylori. The Casp11-/- cells produced less IL-1? indicating that Caspase-11 contributes to IL-1? production in mouse macrophages infected with H. pylori. The main findings of this thesis are that current H. pylori treatment regimens are not sufficient to reach the recommended eradication rate of >90% and alternative treatment strategies should be considered in the Irish context. In relation to host-pathogen interactions, H. pylori-mediated regulation of the Notch signalling pathway, histone modifying components and inflammatory caspases was identified. Further research into these pathways is warranted.
APPROVED
Keywords: Inflammation; Treatment; H. pylori